Formulating nanocomposite materials based on polymers to get high performance and extra properties - Kareem, Awaz Adil; Jaqsi, Mohammed Kadhim; Aziz, Issa Mahdi (Technium Sustainability, 2023)
Nowadays, production nanocomposites based on polymer by blending nanoparticles as a filler with a polymer-matrix had attracted the major concentration of researchers, these materials used now for several modern application and in multiple fields (semiconductors, sensors, photovoltaic cells, optics, electronic-device,…). So it should be concentrated on comprehensive the relation between the polymer-matrix and the nano-particle to achieve more advance in this field. In this paper, the effect of adding SiO2 to PVP/PEO matrix by concentrations are investigated. The optical and thermal properties are evaluated. The properties of the studied films presented the new additions and specifications produced by this process. Briefly, results had shown enhancing in the absorbance, melting-temperature is increased. Additionally, the crystallinity degree of the nanocomposites is examined.